Adsorption Performance of Turmeric as Biosorbent for Free Fatty Acid Removal in Used Cooking Oil - Vika Ayu Devianti; Djamilah Arifiyana; Qurrota A’yuni (Jurnal Penelitian Pendidikan IPA, 2025)
Repeated use of cooking oil produces hazardous compounds such as free fatty acids, carbonyls, and peroxides. This study aims to examine the effectiveness of turmeric as a bio-adsorbent in reducing free fatty acid levels, peroxide numbers, and water content in used cooking oil, and determine the appropriate adsorption isotherm model. Turmeric is one of the biopharmaceutical plants whose availability is quite abundant in Indonesia. Adsorption was carried out with variations in adsorbent mass and contact time. The result showed that turmeric is effective in reducing free fatty acid levels, peroxide value, and water content with adsorption efficiency of up to 54.02, 48.78, and 42.89%, respectively. The adsorption isotherm analysis suggested that the adsorption of free fatty acids followed the Freundlich model rather than the Langmuir model. This study reveals that turmeric has the potential to be a viable bio-adsorbent for enhancing the quality of used cooking oil.